Stigma and the Construction of Self-Concept In Wicked: A Psychological Analysis of Elphaba’s Identity Formation - Nisa, Baiatun; Muslimah, Zahra Izzatul; Susilawati, Susilawati (J-Lalite: Journal of English Studies, 2025)
Stigma is a powerful social and psychological force that shapes how individuals perceive themselves and are perceived by others. While previous studies have frequently explored stigma in realistic or clinical settings, limited attention has been given to how it operates within symbolic or fantastical narratives. This study addresses that gap by examining how stigma influences Elphaba’s self-concept and personality in the film Wicked (2024). The analysis highlights the urgency of exploring cinematic representations of stigma through psychological frameworks, as films often reflect and reshape public understanding of difference and identity. Using a descriptive qualitative method, this research interprets selected scenes and dialogues that depict Elphaba’s experiences of exclusion, conditional acceptance, and identity reconstruction. The study applies the concepts of stigma and self-concept to reveal how social labeling and internalized judgment create incongruence between the self-image and the ideal self, ultimately shaping Elphaba’s moral and emotional development. The findings show that her transformation from self-doubt to self-acceptance represents the psychological negotiation between individuality and social conformity. By connecting personality theory and film analysis, this study expands the discussion of how fictional narratives can illuminate the psychological dynamics of marginalization and resilience, offering new insight into the intersection of stigma, identity, and self-concept in contemporary media.